(untitled) (Medico Legal Update, 2021)
Brain metastasis is one of the most common diagnoses encountered by neurologists, neurosurgeons, radiologists, and oncologists. The aim of this article is to review imaging modalities used in the diagnosis and follow-up of brain metastases. Through the use of various imaging techniques more accurate preoperative diagnosis and more precise intraoperative planning can be made. Post-treatment evaluation can also be refined through the use of these imaging techniques. MRI without and with contrast is the imaging modality of choice in evaluating patients with suspected metastases.28 Head CT is often performed at the initial screening or in an emergency setting to exclude hemorrhage. MRI, however, is superior to CT either without or with contrast in the detection and evaluation of metastases. Metastatic lesions can generally be evaluated with routine contrast MRI studies. Higher dosing of contrast agents, magnetization transfer technique, and higher field strength magnets increase sensitivity. Typical characteristics of metastases, including multiplicity, location, and signal characteristics, together with clinical history, are often sufficient to suggest the diagnosis of metastatic intracranial disease. In the setting of more complex cases or solitary brain metastases, advanced MRI techniques and PET will aid in reaching a diagnosis